THE EFFECT OF CORPORATE GOVERNANCE AND FINANCIAL PERFORMANCE TO THE QUALITY OF CORPORATE SUSTAINABILITY REPORTS - Mutiara Rachma Ardhiani; Aristha Purwanthari Sawitri (Jurnal Ekonomi, 2022)
The focus of this research is to examine how CG affects sustainability report quality using financial performance as a mediator. Companies listed on the Indonesia Stock Exchange for the years 2018 through 2021 made up the study's population. In total, 44 companies made up the study's sample. According to this study's findings, 1) CG has no direct impact on the quality of sustainability reports, 2) CG affects financial performance, 3) financial performance affects the quality of sustainability reports, and 4) CG has an indirect impact on the quality of sustainability reports through the use of financial performance.